Implementation of Free Nutritious Meal Policy to Improve Student Nutrition in Sidoarjo Regency, Indonesia Schools - Adinda Illah Imanda; Qatrunada Suci Salsabila; Arinta Gustinantari Astridia Santosa; Muhammad Roisul Basyar (CV. Era Digital Nusantara, 2026)
Abstract: Nutritional adequacy is a crucial factor in supporting student health, cognitive development, and academic achievement. In Indonesia, nutritional problems among school-aged children continue to be a significant challenge that affects the quality of human resources. To address this issue, the Indonesian government launched the Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) in 2025 as a national policy aimed at improving student nutritional intake. Although the program carries strategic objectives, its implementation across regions demonstrates varying dynamics and challenges. Previous studies have largely emphasized the impact of school feeding programs on nutritional status and learning outcomes, while research focusing on policy implementation processes at the local level in Indonesia remains limited. Purpose: This study aims to analyze the implementation of the Free Nutritious Meal Program as an effort to fulfill student nutritional needs in Sidoarjo Regency. The research adopts a qualitative approach, with data collected through observations, in-depth interviews, and document analysis. Research informants include program beneficiary students, school administrators, Satuan Pelayanan Pemenuhan Gizi (SPPG), and relevant local government agencies. Data analysis is conducted using the Mazmanian and Sabatier policy implementation model, which emphasizes problem characteristics, policy characteristics, and environmental variables. Design/Methodology/Approach: This study employs a qualitative research approach using observations, interviews, and document analysis, guided by the Mazmanian and Sabatier policy implementation framework. Findings: The findings indicate that the implementation of the MBG program in Sidoarjo Regency has generally been conducted fairly well and has received positive responses from students and schools. The program contributes to improving student nutritional intake and reducing their daily expenses. However, several challenges remain, including delays in food distribution, inaccuracies in target school selection, weak inter-institutional coordination, the absence of detailed standard operating procedures, and limited human resource capacity. These issues affect the consistency and effectiveness of program implementation. Originality/value: This study contributes to the development of public policy studies in Indonesia, particularly in relation to the implementation of nutrition fulfillment policies in the education sector. The findings are expected to serve as a reference for evaluation and provide policy recommendations for enhancing the effectiveness and sustainability of the Free Nutritious Meal Program in Indonesia.